Multi-omics analysis of Taiwanofungus gaoligongensis: effects of different cultivation methods on secondary metabolites - He, Tingwen; Yuan, Xiaolong; Xiao, Liangjun; Hu, Tanggeran; Wang, Yi; Zhao, Xiaolei; Li, Lu; Peng, Chengbo; Zhang, Hongling; Zheng, Yuan (Frontiers in Microbiology, 2025)
A multi-omics strategy was utilized in this study to investigate the effects of various cultivation methods—including the fruiting bodies cultivation on Cinnamomum kanehirae wood logs (GLG), the mycelia cultivation on C. kanehirae substrate fungal cultivation bags (NZJB), Cinnamomum camphora substrate fungal cultivation bags (XZJB) and rice medium (DM)—on Secondary Metabolites in Taiwanofungus gaoligongensis. NZJB and XZJB significantly enhanced terpenoids production in the mycelium, with triterpenoid contents in NZJB and XZJB being sevenfold and 3.9-fold higher, respectively, than those in DM. Antcins were notably increased in fungal cultivation bag cultures: antcin C reached the highest level in XZJB (9.72-fold higher than in DM), antcin I peaked in NZJB (12.83-fold higher than in DM), and antrodin C also reached its maximum in NZJB. Additionally, the antrodin C content in NZJB was 3.2-fold higher than in GLG and 4.08-fold higher than in DM. In addition, the levels of steroids, phenolic compounds, and flavonoids were also significantly increased in NZJB and XZJB. Transcriptome analysis revealed significant differences in the expression of genes involved in the biosynthesis of antcins and antrodin C across the different cultivation methods. In particular, the expression of TgHMGR was markedly higher in NZJB than in XZJB and DM, correlating with the elevated terpenoids and triterpenoids levels, suggesting that TgHMGR may act as a key rate-limiting enzyme in the terpenoid biosynthesis pathway of T. gaoligongensis. The expression levels of terpenoid biosynthesis-related genes were significantly elevated in GLG compared to mycelium, consistent with the higher abundance of terpenoid metabolites. Co-expression analysis of transcription factors (TFs) and promoter binding site predictions indicated that the expression of TgHMGR and TgFPPS 2 may be regulated by TgHSF4 and TgMYB6, respectively. Meanwhile, the expression of TgErg2, TgErg3, TgErg5, and TgErg6 1 may be regulated by TgZnF1, TgMYB9, TgHOX1, and TgHMG8. This study compared the metabolite profiles and gene expression patterns of the fruiting bodies of T. gaoligongensis with those of three types of cultivated mycelia. The results provide new insights into the transcriptional regulation of key bioactive compound biosynthesis in T. gaoligongensis and suggest potential strategies to enhance the production of active compounds in mycelia through artificial cultivation, thereby improving its medicinal value and production efficiency.